Developing Differentiated Teaching Modules in Indonesian Language Learning for Students with Attention Deficit Hyperactivity Disorder - Harahap, Dedek Afrida; Kartolo, Rahmat; Sutikno; Susanti, Dewi; Sibarani, Asni (ITScience (Information Technology and Science), 2025)
A differentiated teaching module, developed systematically and contextually over five sessions improve the language skills. The development of a differentiated teaching module in Indonesian language learning had a positive impact on students with ADHD. The paper aims to design to accommodate diverse student learning characteristics, taking into account content, processes, and learning products. The research is qualitative, supported by R&D and ADDIE models as techniques. The population includes all students with ADHD problems at a state school, and there are only two students classified in the sample. Data are collected through observation and in-depth interviews; both are conducted with classroom teachers, the teachers’ group, and parents. A documentation study also assists data collection. Focus is given on students’ attention, interaction, social skills, and engagement during learning, interviews, and the Indonesian language test. Data analysis technique uses qualitative methods in three stages: data reduction, data presentation, and conclusion. The research reveals several challenges in implementing the differentiated teaching module. Teachers face obstacles in adapting learning strategies to students’ needs, especially in heterogeneous classrooms. Further training is needed for teachers to implement differentiated learning methods. With the teaching module, schools can improve the quality of inclusive education for their students, enabling them to obtain a more optimal learning experience. This research also emphasizes the importance of collaboration between teachers, parents, and the school in supporting students’ academic and social development with ADHD through a more flexible and responsive learning approach to their needs.